Digital signal processing for UWB radar - Maung Kyaw Lin Soe. (2008)
This dissertation presents the simulation study of using an ultra-wideband (UWB) radar for locating objects within or behind the wall. The UWB radars are useful in a number of applications and through-wall imaging is one of them. It can be used in search and rescue missions, behind the wall target detection, surveillance, object sensing through smoke and dust columns, etc.